Efektivitas Menghafal Al-Qur’an dalam Meningkatkan Kecerdasan Emosional Anak Yatim di Pesantren Yatim Cahaya Madinah Tangerang Selatan - Mawaddah Warohmah; Muh. Ubaidillah Al Ghifary Slamet; Pahruraji Pahruraji (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the emotional intelligence of orphans through the activity of memorizing the Qur'an at the Cahaya Madinah Orphanage Boarding School, South Tangerang, elaborate on the implementation of memorizing the Qur'an at the Cahaya Madinah Orphanage Boarding School, South Tangerang, and analyze the supporting and inhibiting factors. The type of this research uses qualitative research with a descriptive approach. The primary data sources are from the caretakers of the Islamic boarding school, tahfizh instructors, heads of the Islamic boarding school, dormitory instructors, and orphan students who live in the Cahaya Madinah Orphanage Boarding School, Pondok Cabe, South Tangerang. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that, 1) The tahfizh activities of the Qur'an implemented at the Cahaya Madinah Orphanage Boarding School include: increasing memorization (ziyadah), repeating memorization (muroja'ah), a juz increase exam system, weekly student sima'an activities, and memorization exams with multiples of five juz in one sitting. 2) Memorizing the Qur'an can improve the emotional intelligence of orphans at the Cahaya Madinah Orphanage Pondok Cabe Tangerang Selatan, this can be seen from aspects of emotional intelligence including self-awareness, self-regulation, self-motivation, empathy, and their increasing social skills. 3) The supporting factors are having a strong desire to memorize, remembering the privilege of memorizing the Qur'an, having support from the family, having support from teachers, a supportive environment, having a tahfizh exam, holding positive activities. While the inhibiting factors are laziness, drowsiness, family problems, difficulty in memorizing, not participating in activities or running away, and poor time management.